Factors Associated with the Preparedness for Birth of Primigravida Pregnant Women at the Kamonji Health Center, Palu City - Ketut Suarayasa; I Putu Fery Immanuel White; Junjun Fitriani; Bertin Ayu Wandira (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
Background: For a mother-to-be, the first pregnancy is a new journey marked by significant physical and psychological changes, causing anxiety in itself. This anxiety can arise because of the long period of waiting for birth and images of scary things during the birth process, even though they may not necessarily happen. Objective: The objective of this research is to find out factors related to the readiness for delivery of primigravida women at the Kamonji Public Health Centre, Palu City Methods: This research used a descriptive-analytical design using a Cross Sectional approach. The population of this research was 142 primigravida women in the working area of the Kamonji Public Health Centre, Palu City, and then used as the research sample a total of 59 respondents who were selected using Non-Probability Sampling by purposive sampling. Data were collected using questionnaires. Results: The results of the bivariate analysis show that there is a relationship between the age and the childbirth readiness of primigravida women with a value of p = 0.042. There is a relationship between the education level and the readiness of primigravida women with a value of p = 0.033. There is a relationship between the husband's support and the childbirth readiness of primigravida women with a value of p = 0.036. There is a relationship between emotional maturity and the childbirth readiness of primigravida women with a value of p = 0.036. Conclusion: Based on the results above, the research concludes that there is a relationship between age, education level, husband support, emotional maturity factors and the childbirth readiness for primigravida women at the Singgani Public Health Clinic.